The influence of a chemical treatment plant and an existing wetland ecosystem on AMD pollution and water quality along the Blesbokspruit, South Africa - Lourenco, Mauro (My University, 2019)
The influence of the Eastern Basin Acid Mine Drainage (AMD) chemical treatment plant and the Blesbokspruit Wetland ecosystem in remediating AMD pollution has been determined. The research process involved making land use maps, using historical Rand Water quality data, and collecting water, sediment and soil samples along the Blesbokspruit. Being in operation since August 2016, the Eastern Basin chemical AMD treatment plant has had a major influence on water quality, and this influence is not entirely positive. The introduction of the treatment plant was completely necessary at the time due to the possible decant of AMD water from the abandoned Grootvlei mine into the Blesbokspruit wetland. However, phase one of treatment which makes use of chemical mechanisms to firstly neutralise the water with lime and thereafter remove the toxic metals that precipitate out of the solution has negatively influenced conductivity, magnesium, chloride and sulphate levels downstream. Over time, the concentrations of these parameters have increased to worse management level targets set out by the Blesbokspruit Forum. Conductivity and sulphate have reached unacceptable management target levels since the introduction of the chemical treatment plant. The reduction of iron, manganese, ammonium, nitrate and phosphate downstream of the AMD treatment plant is due dilution caused by increased discharge from the treatment plant and due to the wetland ecosystem removing these contaminants. The greater Blesbokspruit Wetland and the Marievale Wetland have a very low influence on improving water quality within the area. The wetlands do reduce nutrient levels according to Rand Water data, but the water quality in this study area is mainly influenced by what is occurring upstream of the wetlands at the AMD treatment plant. There are numerous environmental concerns within this study area which includes the Marievale Bird Sanctuary. Soil quality results suggest that the Blesbokspruit has a high influence on soil conductivity. River sediment heavy metal analysis results suggest that the river sediments collected from the eight sampling sites are highly polluted and have a low to moderate potential for ecotoxicity. Sediment trace metal concentrations are also highly concentrated near mine dumps and historical mine decant points. Increased soil conductivity and heavy metal contamination may have a negative impact on the waterfowl living at the Marievale Bird Sanctuary. Ground truth water sampling also identified that there is a seasonal signal of increased conductivity and sulphate during the dry winter months. The results of this research have highlighted the need for phase two of treatment (which would implement desalination infrastructure) to begin at the chemical AMD treatment plant as well as increased monitoring and protection of the wetland ecosystem within the study area.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, for the Master of Science in the School of Geography, Archaeology and Environmental Studies, November 2019
Keywords: Acid mine drainage; Acid mine drainage--South Africa; Acid mine drainage--Environmental aspects